Mechanisms underpinning the efficacy of faecal microbiota transplantation in treating gastrointestinal disease - Segal,JP; Mullish,BH; Quraishi,MN; Iqbal,T; Marchesi,JR; Sokol,H (Therapeutic Advances in Gastroenterology, 2020)
Faecal microbiota transplantation (FMT) is currently a recommended therapy for recurrent/refractory Clostridioides difficile infection (CDI). The success of FMT for CDI has led to interest in its therapeutic potential in many other disorders. The mechanisms that underpin the efficacy of FMT are not fully understood. Importantly, FMT remains a crucial treatment in managing CDI and understanding the mechanisms that underpin its success will be critical to improve its clinical efficacy, safety and usability. Furthermore, a deeper understanding of this may allow us to expose FMT’s full potential as a therapeutic tool for other disease states. This review will explore the current understanding of the mechanisms underlying the efficacy of FMT across a variety of diseases.